Find the numerical equivalent of 9^9 x 9^-6 Your answer should be written WITHOUT exponents.

1 answer

To find the numerical equivalent of \( 9^9 \times 9^{-6} \), we can use the properties of exponents. Specifically, we can combine the exponents when the same base is being multiplied:

\[ 9^9 \times 9^{-6} = 9^{9 + (-6)} = 9^{9 - 6} = 9^3 \]

Now we need to calculate \( 9^3 \):

\[ 9^3 = 9 \times 9 \times 9 \]

Calculating this step by step:

  1. \( 9 \times 9 = 81 \)
  2. \( 81 \times 9 = 729 \)

Thus, the numerical equivalent of \( 9^9 \times 9^{-6} \) is

\[ \boxed{729} \]